2019
DOI: 10.3390/en12101942
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Power Production Costs in a Wind Power Plant–Flywheel Energy Storage System Arrangement

Abstract: The paper presents issues of optimisation of a wind power plant–energy storage system (WPP-ESS) arrangement operating in a specific geographical location. An algorithm was developed to minimise the unit discounted cost of electricity generation in a system containing a wind power plant and flywheel energy storage. In order to carry out the task, population heuristics of the genetic algorithm were used with modifications introduced by the author (taking into account the coefficient of variation of the generatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Figure 11 depicts different types of control strategies. Operation and maintenance variable ($/kWh) (300-1000) 124 (3000-6000) 124 (5.6) 2 (0.0003) 125 (250-350) 2 (1000-5000) 126 (130-500) 125 (7800-8800) 127 (1950-2200) 127 Hybridizing FESS with one or more ESSs while operating in a power system requires simultaneous charging and discharging phenomenon. 148 In this regard, authors have suggested the control of FESS based on SoC.…”
Section: Control Approach Stability Enhancement and Maintenance Of Fessmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 11 depicts different types of control strategies. Operation and maintenance variable ($/kWh) (300-1000) 124 (3000-6000) 124 (5.6) 2 (0.0003) 125 (250-350) 2 (1000-5000) 126 (130-500) 125 (7800-8800) 127 (1950-2200) 127 Hybridizing FESS with one or more ESSs while operating in a power system requires simultaneous charging and discharging phenomenon. 148 In this regard, authors have suggested the control of FESS based on SoC.…”
Section: Control Approach Stability Enhancement and Maintenance Of Fessmentioning
confidence: 99%
“…FESS is found to be the cheapest ESS which involves high output power. FESS is mostly employed for transmission and distribution purposes 123 . Table 4 highlights the overall cost analysis for FESS.…”
Section: Cost Model Of Fessmentioning
confidence: 99%
“…The first electrochemical cells were designed, built and described more than 200 years ago, but it was only in the last three decades that the emergence of lithium-ion cells contributed to the dynamic growth of their popularity. The areas of their application are constantly expanding, and the most common are currently mobile electronic devices, various types of e-mobility solutions (especially electric vehicles), uninterruptible power supply systems, and systems cooperating with renewable sources of electricity [1]. Where the cost of cell purchase is significant and the load is characterized by high dynamics of change, the analysis of cell behaviour, both in electrical and thermal aspects, is very important [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Many factors, such air density around the wind farms and wind turbine characteristics, have an impact on the wind energy production. The use of energy storage systems can eliminate short-term disconnections from the grid of wind-energy sources [1]. Specifically, the amount of energy in wind is related with the cubic of the wind speed [2].…”
Section: Introductionmentioning
confidence: 99%